Optimalisasi Kompetensi Individu di Era Pandemi melalui Edukasi Daring: Competence Optimalization in the Pandemic Era through Online Education - Gita Aulia Nurani; Susatyo Yuwono; Rizqi Zulfa Qatrunnada; Achmad Dwityanto Oktaviansyah; Nureyzwan Sabani; Darajatun Surya Admaja; Galang Setyo Pambudi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
The pandemic situation and digital acceleration have altered ideas on the significance of competence. Various offline restrictions that occur can be utilized to maximize previously acquired competencies. Individuals are responsible for their competency development and must take the initiative to use it. However, this does not preclude the potential that this may occur in response to commands from superiors. This community service aims to provide education on how to maximize competency and the types of activities that may be conducted via the online platform Zoom. A total of 97 workers or employees from various fields participated in the activity. The effectiveness of the activity can be determined by evaluating the activity's participants. According to the evaluation results, 88.2% of the participants thought there was greater insight regarding relevant competencies. The following recommendation for education providers is to investigate offline implementation if situations permit overcoming the restrictions of resource-participant contact.